Pengenalan Bahasa Arab melalui Nyanyian pada Anak Usia Prasekolah di PAUD Terpadu Ihyaul Ulum Puncu Kediri Jatim - Khoiruddin Khoiruddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
The purpose of the event is to introduce Arabic through singing at early childhood in Education Ihyaul Ulum Gadungan Puncu Kediri Integrated School, and know the process of learning to teach Arabic through singing. The research method used a descriptive analysis of the activities undertaken in an effort to improve the ability to recognize Arabic language in early childhood. The process is done by using several methods such as singing while playing and singing using the movement and singing using the learning media. The conclusion of this activity is; (1) through singing with the method of play is singing with the movement, then pre-school children can easily recognize the vocabulary of Arabic, (2) Kindergarten children have a high interest in knowing Arabic. This can be seen from children's enthusiasm when singing familiar Hymnic songs, and (3) The content of short songs and easy-to-use language so that students easily digest and